La verifica incerta verifica incerta, 1964 - 1965 ; (JPR Ringier, 2014)
The history of the fertile but ambiguous relationship between visual arts and cinema during the 20th century is punctuated by a number of landmarks: 'Verifica Incerta' released in 1964 by Italian artists Gianfranco Baruchello and Alberto Griffi is one such, even if it has been overlooked for several decades. Inspired by Marcel Duchamp and supported by John Cagethe film was premiered in Paris at La Cinémathèque française and in New York at The Museum of Modern Art'Verifica Incerta' is the perfect offspring from the encounter between Cinecittà and avant-garde expression; it is also one of the very first examples of a film using found footage. An assemblage of extracts taken from 450,000 feet of footage from the 1950s purchased by the artists before their destruction, it is a schizophrenic yet ironic kaleidoscope about mass cinema and B-movies. Without any script or plot, it is an encyclopedia of leftovers, a deconstructed attempt to rediscover Hollywood, a linguistic experiment in film and montage. As art and cinema critic Carla Subrizi writes: "'Verifica Incerta' questions time and movement through images, creating a system that it is not internal to the single shots but rather external: it is the process of selecting, editing, discarding, recomposing that creates a new conception of time. Rhythm, duration, stopping and starting, distance: the images are used as ready-mades and placed in a different order through montage; they abandon their original meaning and gain a different and uncanny one."